2020
DOI: 10.1128/jb.00114-20
|View full text |Cite
|
Sign up to set email alerts
|

Dps Protects Enterohemorrhagic Escherichia coli against Acid-Induced Antimicrobial Peptide Killing

Abstract: Dps, a DNA-binding protein from starved cells in Escherichia coli, is part of the bacterial defense system that protects DNA against various cellular stresses. Our lab previously demonstrated that a novel antimicrobial peptide, WRWYCR, enhances acid-induced killing of enterohemorrhagic Escherichia coli (EHEC) and ameliorates infection in a Citrobacter rodentium mouse model of EHEC infection. WRWYCR has previously been shown to compromise DNA damage repair and to increase chelatable iron within the cell. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The catalase KatG and the alkyl hydroperoxide-NADPH oxidoreductase AhpCF are involved in the degradation of endogenous peroxide [49]. Dps can directly bind DNA to form a highly stable complex resistant to acid, base and oxidative stresses, and together with YaaA can sequester intracellular unincorporated iron [50][51][52]. The Suf proteins are also required by E. coli for rebuilding iron-sulfur clusters that have been oxidatively damaged [49,53].…”
Section: Stress Responsive Genes Are Activated All Along the Gitmentioning
confidence: 99%
“…The catalase KatG and the alkyl hydroperoxide-NADPH oxidoreductase AhpCF are involved in the degradation of endogenous peroxide [49]. Dps can directly bind DNA to form a highly stable complex resistant to acid, base and oxidative stresses, and together with YaaA can sequester intracellular unincorporated iron [50][51][52]. The Suf proteins are also required by E. coli for rebuilding iron-sulfur clusters that have been oxidatively damaged [49,53].…”
Section: Stress Responsive Genes Are Activated All Along the Gitmentioning
confidence: 99%
“…DNA-binding protein Dps is involved in the protection of bacterial cells from various types of stresses, primarily oxidative and starvation stress, as a result of which the protein copy synthesis increases to 150–200 thousand [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. It has been shown that it protects bacteria from heat and alkaline shocks, high pressure, toxic effects of heavy metals, UV and gamma radiation, and other types of negative effects [ 13 , 15 , 18 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%